Toxicity assessment and degradation of disperse azo dyes by photoelectrocatalytic oxidation on ti/tio2 nanotubular array electrodes - Osugi, M. E. [UNESP]; Zanoni, M. V.B. [UNESP]; Chenthamarakshan, C. R.; De Tacconi, N. R.; Woldemariam, G. A.; Mandal, S. S.; Rajeshwar, K. (Sycamore Global Publications, 2008)
The feasibility of photobleaching and detoxification of three disperse azo dyes, namely, Disperse Orange 1, Disperse Red 1 and Disperse Red 13, in 0.1 mol L-1 Na2SO4 containing anionic surfactant was investigated using Ti/TiO2 nanotubular array electrodes prepared by the electrochemical anodization of Ti foil. The results were compared with nanoporous Ti/TiO2 electrodes prepared by the sol-gel method. After 60 min of photoelectrocatalytic oxidation of solutions containing 5.0 x 10 -5 mol L-1 of Disperse Red 1, Disperse Orange 1 and Disperse Red 13 and 80 mg L-1 of anionic surfactant (Emulsogen) under UV light and an applied potential of +1.0 V (vs. Ag|AgCl|satd. KCl reference electrode), 100% of discoloration was obtained for all the dyes investigated. The rate constants for the nanotubular TiO2 array were almost 2-3 times higher for the photoelectrocatalytic removal of these dyes compared to their sol-gel derived counterparts. Measurement of TOC removal showed ca. 70% reduction after 3 h of photoelectrocatalytic oxidation and the HPLC chromatograms presented complete extinction ofthe signals. All the samples ofdyes extracted in organic phase, without surfactant influence, presented lower toxicity when submitted to photoelectrocatalytic oxidation suggesting that this process would be a good option to remove disperse azo dyes from aqueous media and decrease their cytotoxicity. However it is worth noting that the Emulsogen anionic surfactant presented an increase in the acute toxicity for human embryonic kidney (HEK293) cells even after photoelectrocatalysis and indicates the requirement of other auxiliary procedures before its own release to the aquatic environment. These results underline the need for caution in interpreting toxicity data when a surfactant is also present in addition to an organic dye. © 2008 Science & Technology Network, Inc.
Keywords: Anodization; Azo dye; Cytotoxicity; Organic dye; Photocatalytic oxidation; Sol-gel chemistry